Pencapaian Tugas Perkembangan Remaja Ditinjau dari Kematangan Intelektual di SMP N I Sasak Ranah Pasisia Kabupaten Pasaman Barat - Sinne, Defria; Santosa, Budi (Lembaga Yasin AlSys, 2023)
Based on the reality at SMPN 1 Sasak Ranah Pasisia. students who are not satisfied with their grades, and students must think about how so that students can solve these problems and understand what the teacher explained. for example learning in class students do not understand what the teacher explained, the purpose of the research is so that students understand what the teacher explains and students can solve their own problems. This research is a descriptive research. This study has a population of 123 students and a sample of 30 students. Data collection techniques in this study using Random Sampling Techniques. The data analysis technique uses manual processing of ITP results (Development Task Inventory). Based on the research conducted, the results show that the level of developmental tasks is a continuum structure of self-development from simple to complex. In general, the developmental level of elementary school children is between 1 and 4, junior high school aged children between 2 and 5, high school aged children between 3 and 6, and student age levels between 4 and 7.